Anisotropic transport of normal metal-barrier-normal metal junctions in monolayer phosphorene. (12th June 2017) - De Sarkar, Sangita; Agarwal, Amit; Sengupta, K
Abstract: We study transport properties of a phosphorene monolayer in the presence of single and multiple potential barriers of height U 0 and width d, using both continuum and microscopic lattice models, and show that the nature of electron transport along its armchair edge ( x direction) is qualitatively different from its counterpart in both conventional two-dimensional electron gas with Schrödinger-like quasiparticles and graphene or surfaces of topological insulators hosting massless Dirac quasiparticles. We show that the transport, mediated by massive Dirac electrons, allows one to achieve collimated quasiparticle motion along x and thus makes monolayer phosphorene an ideal experimental platform for studying Klein paradox in the context of gapped Dirac materials. We study the dependence of the tunneling conductance G ≡ G x x as a function of d and U 0, and demonstrate that for a given applied voltage V its behavior changes from oscillatory to decaying function of d for a range of U 0 with finite non-zero upper and lower bounds, and provide analytical expression for these bounds within which G decays with d . We contrast such behavior of G with that of massless Dirac electrons in graphene and also with that along the zigzag edge ( y direction) in phosphorene where the quasiparticles obey an effective Schrödinger equation at low energy. We also study transport through multiple barriers along x and demonstrate that these properties hold for transport through multiple barriers as well. Finally, we suggest concrete experiments which may verify our theoretical predictions.